IMPLEMENTASI PRAKTIKUM PEMBELAJARAN PAI DI SEKOLAH MENENGAH ATAS PADA MASA PANDEMI COVID-19 - Savira Azka Wulandari, - (2021)
The implementation of Islamic Religion Education (PAI) education during Covid-19 pandemic is still important to be conducted, given the learning objectives of PAI which include cognitive, affective, and psychomotor aspects. However, there are some problems that still occurred such as, the majority of PAI teacher focuses much on theory without conducting any practicum, the limited time allocation for PAI, unprofessional PAI teachers, along with the Covid-19 pandemic that has become a new challenge in implementing PAI practicum. Therefore, this research was generally carried out to describe the implementation of PAI learning practicum at SMAN 1 Subang during the Covid-19 pandemic. This study used a qualitative approach with descriptive methods. Researcher is the key instrument in this research. The data collection techniques used in this study were interview, observation and documentation study. Analysis of research data was carried out in the form of data reduction, data display, and verification. The results of the research are: 1) The types of PAI learning practicum carried out namely: writing, reading, and memorizing Al-qur'ān, memorizing dua after duha prayer, hajj and umrah, and marriage, 2) Lesson Planning for PAI learning practicum in general has been well planned, but the lesson plans need to be developed optimally, 3) The facilities used mostly by teachers in the PAI learning practicum are WhatsApp and Google classroom applications, because they are easy to use and free, 4) The implementation of PAI learning practicum reflected the Multi-synchronous type of learning, which is the combination of a Synchronous combination (Video conference Zoom Meeting) and Asynchronous (WhatsApp, Google Classroom, telegram, and e-mail), 5) Assessment of PAI learning practicum was carried out using 3 assessment methods, namely: direct tests (video and portfolio assignments) and written reports sent to a WhatsApp group.